The roles of political and business ties in new ventures: Evidence from China - Lin, Ya-Hui; Chen, Chung-Jen; Lin, Bou-Wen (Asian business & management, 2014)
This study investigates how political and business ties affect new-venture performance in China. Findings from the archival data of 105 Chinese new ventures indicate that political ties positively relate to new-venture performance, whereas business ties do not. More importantly, this research presents a contingent view of political and business ties and offers evidence that these ties can lead to greater new-venture performance when the new venture has a higher level of outward growth orientation. The external ties/new-venture performance links emerge as more complex than prior studies have shown.